Preparation for and Implementation of Shared Medical Appointments to Improve Self-Management, Knowledge, and Care Quality Among Patients With Atrial Fibrillation - Joan M. Griffin, PhD; Lynette G. Stuart-Mullen, MSN, APRN, CNS; Monika M. Schmidt, DNP, APRN, AGNP-C; Pamela J. McCabe, PhD, APRN, CNS; Thomas J. O'Byrne, BS; Megan E. Branda, MS; Christopher J. McLeod, MBChB, PhD, FHRS (Mayo Clinic Proceedings: Innovations, Quality & Outcomes, 2018)
Atrial fibrillation (AF) is the most common cardiac arrhythmia in adults and is associated with an increased risk of stroke, heart failure, and death. Therapy for this pervasive arrhythmia is complex, involving multiple options that chiefly manage symptoms and prevent stroke. Current therapeutic strategies are also of limited efficacy, and can present potentially life-threatening side effects and/or complications. Emerging research suggests that the burden of AF can be reduced by improving patient understanding of the arrhythmia and teaching patients to adopt and maintain lifestyle and behavior changes. Shared medical appointments (SMAs) have been successfully used to deliver education and develop patient coping and disease management skills for patients with complex needs, but there is a paucity of studies examining the use of SMAs for managing AF. Moreover, few studies have examined strategies for implementing SMAs into routine clinical care. We detail our approach for (1) adapting a patient-centered SMA curriculum; (2) designing an evaluation comparing SMAs to routine care on patient outcomes; and (3) implementing SMAs into routine clinical practice. We conclude that evaluation and implementation of SMAs into routine clinical practice requires considerable planning and continuous engagement from committed key stakeholders, including patients, family members, schedulers, clinical staff, nurse educators, administrators, and billing specialists.